2020
DOI: 10.3390/molecules25214965
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Polyhedral Oligomeric Silsesquioxane Porphyrin Derivatives on Photodynamic Therapy

Abstract: Polyhedral oligomeric silsesquioxane (POSS) is a promising scaffold to be used as delivery system. POSS can modify the properties of photosensitizers to enhance their efficacy toward photodynamic therapy (PDT). In this work, we designed, synthesized and characterized five different POSS porphyrin (POSSPs 1–5) derivatives containing hydrophobic (1–3) and hydrophilic (4 and 5) functional groups. In general, all the POSSPs showed a better singlet oxygen quantum yield than the parent porphyrins due to the steric h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Recently, ferroptosis has also been associated with PDT [ 16 , 24 , 25 ]. Our group has focused on the development of PSilQ nanoparticles as a photosensitizer-delivery platform for PDT [ 5 , 6 , 7 , 8 , 9 , 26 ]. We have already demonstrated that PSilQ nanoparticles carrying PpIX as a photosensitizer induce phototoxicity through apoptotic and necrotic cell death mechanisms [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ferroptosis has also been associated with PDT [ 16 , 24 , 25 ]. Our group has focused on the development of PSilQ nanoparticles as a photosensitizer-delivery platform for PDT [ 5 , 6 , 7 , 8 , 9 , 26 ]. We have already demonstrated that PSilQ nanoparticles carrying PpIX as a photosensitizer induce phototoxicity through apoptotic and necrotic cell death mechanisms [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, our group synthesized octa(aminopropyl)-POSS using APTES as a silica precursor. The octa(aminopropyl)-POSS was reacted with carboxy(phenyl)-triphenyl porphyrin via an amidation reaction to afford a porphyrin-POSS molecule [27]. Also, Hörner and co-workers used octa(aminopropyl)-POSS as a starting material to be modified with fluorescent tetramethyl-rhodamide.…”
Section: Sol-gel Synthetic Protocols For Possmentioning
confidence: 99%
“…For instance, our group used this strategy to afford aminopropyl-hepta(isobutyl)-or aminopropyl-hepta(phenyl)-POSS from the corresponding trisilanol POSS precursors. These molecules were further modified to finally obtain porphyrin-POSS molecules [27]. Using the corner capping strategy, Ervithayasuporn and co-workers reacted 3-chloropropyltrhichlorosilane with hepta(isobutyl)-trisilanol POSS to obtain a cage with only one chloropropyl functionality, that was later subjected to an azidation with excess NaN 3 in DMF-THF (93% yield).…”
Section: Corner Capping Of Partially Condensed Possmentioning
confidence: 99%
See 2 more Smart Citations